The Smad Dependent TGF-β and BMP Signaling Pathway in Bone Remodeling and Therapies - Zou, Ming-Li; Chen, Zhong-Hua; Teng, Ying-Ying; Liu, Si-Yu; Jia, Yuan; Zhang, Kai-Wen; Sun, Zi-Li; Wu, Jun-Jie; Yuan, Zheng-Dong; Feng, Yi; Li, Xia; Xu, Rui-Sheng; et al. (Frontiers in Molecular Biosciences, 2021)
Bone remodeling is a continuous process that maintains the homeostasis of the skeletal system, and it depends on the homeostasis between bone-forming osteoblasts and bone-absorbing osteoclasts. A large number of studies have confirmed that the Smad signaling pathway is essential for the regulation of osteoblastic and osteoclastic differentiation during skeletal development, bone formation and bone homeostasis, suggesting a close relationship between Smad signaling and bone remodeling. It is known that Smads proteins are pivotal intracellular effectors for the members of the transforming growth factor-β (TGF-β) and bone morphogenetic proteins (BMP), acting as transcription factors. Smad mediates the signal transduction in TGF-β and BMP signaling pathway that affects both osteoblast and osteoclast functions, and therefore plays a critical role in the regulation of bone remodeling. Increasing studies have demonstrated that a number of Smad signaling regulators have potential functions in bone remodeling. Therefore, targeting Smad dependent TGF-β and BMP signaling pathway might be a novel and promising therapeutic strategy against osteoporosis. This article aims to review recent advances in this field, summarizing the influence of Smad on osteoblast and osteoclast function, together with Smad signaling regulators in bone remodeling. This will facilitate the understanding of Smad signaling pathway in bone biology and shed new light on the modulation and potential treatment for osteoporosis.